Mapping the Mechanism for Trade Dispute Resolution in the Bilateral Free Trade Agreement Between Indonesia and Partner Countries - Wiko, Garuda; Kinanti, Fatma Muthia (UI Scholars Hub, 2026)
Indonesia actively promotes international trade liberalization through various free trade agreements (FTAs) with partner nations. This study focuses on the dispute settlement mechanisms (DSM) within Indonesia’s bilateral FTAs, given that most partners are members of the World Trade Organization (WTO), making this relevant comparison. The research is divided into three main parts: explaining international trade dispute settlement mechanisms, mapping DSMs in Indonesia’s FTAs, and a comparative analysis. It aims to answer how dispute settlement mechanisms are structured in Indonesia’s bilateral FTAs. Based on the mapping, it is found that the majority of Indonesia’s bilateral FTAs align with WTO dispute resolution methods, but it lacks appellate mechanisms. The DSM in bilateral FTAs can be an alternative to resolve trade disputes to obtain a more final and binding decision, considering that all FTAs only use first-level adjudication. This is significant, especially with the WTO Dispute Settlement Body (DSB) experiencing panel member vacancies, rendering the appeals process obsolete.